2014
DOI: 10.7314/apjcp.2014.15.5.2195
|View full text |Cite
|
Sign up to set email alerts
|

Ten Year Experience with Surgery and Radiation in the Management of Malignant Major Salivary Gland Tumors

Abstract: Background: Despite being rare in incidence, malignant tumors of major salivary glands show diverse histological variation. There are limited data on major salivary gland tumor management and outcome from Pakistan. The objective of this study was to share our experience with management of malignant tumors of major salivary glands. Materials and Methods: Patients who received treatment at Shaukat Khanum Cancer Hospital and Research Center from July 2002 to June 2011 with an underlying diagnosis of a major saliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
16
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 27 publications
(28 reference statements)
4
16
0
12
Order By: Relevance
“…(Teo et al, 2000). A recent study by Iqbal et al showed that grade was the only independent predictor of disease free survival and nodal involvement was the only independent predictor of overall survival (Iqbal et al, 2014). Patients with adenoid cystic carcinoma of the major salivary glands treated with surgery and radiation have excellent overall control rates with 5 and 10 year local control rates of 94% and 73% (Theresa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…(Teo et al, 2000). A recent study by Iqbal et al showed that grade was the only independent predictor of disease free survival and nodal involvement was the only independent predictor of overall survival (Iqbal et al, 2014). Patients with adenoid cystic carcinoma of the major salivary glands treated with surgery and radiation have excellent overall control rates with 5 and 10 year local control rates of 94% and 73% (Theresa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to studies demonstrating MEC as the most prevalent tumor in literature there were also investigators who found different results. The rates reporting MEC as the 1st most prevalent tumor among series were 60% (Vargas et al, 2002), 31.7% (Lima et al, 2005), 60% (Ali et al, 2010), and 20% (Kizil et al, 2013), and 43% (Iqbal et al, 2014). Some authors (Gunizi and Guney, 2013) reported the MEC frequency at an equal rate with SqCC (21.8%), while other authors reported it as the 2nd most prevalent tumor with 25% after SqCCa.…”
Section: Discussionmentioning
confidence: 97%
“…And almost 20% of that patients have been cured with RT alone [29]. Therefore, RT is now widely conducted in inoperable and postoperative salivary MEC and the results were reported as effective palliation and disease control [30,31].…”
Section: Discussionmentioning
confidence: 99%